Kompetensi dan Kinerja Auditor: Peran Moderasi Struktur Audit dan Supervisi Audit - Leny Pebriyaningrum, Ni Made; Dwirandra, A. A. N. B (E-Jurnal Akuntansi; Vol 30 No 11 (2020)DO - 10.24843/EJA.2020.v30.i11.p13, 2020)
The purpose of this study was to determine the moderation of the audit structure and audit supervision on the effect of competence on auditor performance. The location of this research was conducted at the Public Accounting Firm (KAP) of the Province of Bali. This research data uses primary data that is processed through the distribution of questionnaires with data analysis techniques using moderation regression analysis. The results of this study indicate that competence has a positive effect on auditor performance. The results showed that the audit structure strengthened the positive effect of competence on auditor performance in the Public Accounting Firm. The results also showed that audit supervision strengthened the positive effect of competence on auditor performance in the Public Accounting Firm. Keywords: Audit Structure; Audit Supervision; Competence; Auditor Performance.